Analisis tingkat kesehatan bank dengan menggunakan metode risk-based bank rating - Hanny Syaiedah; Zainal Ilmi; Maryam Nadir (Jurnal Ilmu Manajemen Mulawarman (JIMM), 2018)
This study aims to determine : 1) Bank Health level in terms of risk profile on state-owned banks period 2012-2015, 2) Bank Health rating in terms of Good Corporate Governance factor in government-owned banks period 2012-2015, 3) Bank soudness level in terms of earnings factor in state-owned banks period 2012-2015, 4) Bank Soudness level in terms of capital factor in state-owned banks period 2012-2015, and 5) Bank soudness–owned level in terms of risk profile, Good Corporate Governance, Earnings, dan Capital in state-owned banks period 2012-2015. The object of this research is all goverment-owned banks such as: PT Bank Mandiri, PT Bank Negara Indonesia, PT Bank Rakyat Indonesia, PT Bank Tabungan Negara. The research data is obtained from the web of Bank Indonesia which has published the audited financial statements of the Bank in 2012-2015 and it’s official website of the Bank concerned. The sampling used is a saturated sampling technique that is the technique of determining the sample when all members of the popilations used in this study is the method of documentation. This research use qualititative descriptive data analysis ratio analysis : (1) Risk Profile using  NPL and LDR , (2) Good Corporate Governance, (3) Earnings using financial ratio of ROA and NIM, dan (4) Capital using financial ratio of CAR. The results of research indicate in the periode 2012-2015 overall Banks studied have a very healthy predicate. The risk profile factor shows Non Bank Performing Loan below 5% and the majority of Bank LDR is predicated healthy. The Good Corporate Governance factor shows that Bank gets very good predicate. The Earning factor shows Bank ROA of more than 1,5% and NIM Bank is more than 3%. The capital factor shows that the CAR of Bank is more than 12% so that it can fulfill the minimum capital requirement of 8%.